1990
DOI: 10.1007/bf00018641
|View full text |Cite
|
Sign up to set email alerts
|

Lignicolous marine fungi in the Straits of Messina, Italy

Abstract: The occurrence and distribution of lignicolous marine fungi in the Straits of Messina has been studied. Using submerged panels of pine, beech and poplar, twenty fungal species were identified. The lignicolous mycoflora of the Messina Straits was not significantly different from that reported in the literature for other temperate marine coastal environments, Ascomycotina being frequent, while Basidiomycotina were rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Initialy this was focused on temperate water fungi, especially wood-inhabiting taxa (Jones 1968;Schaumann 1968Schaumann , 1969Schaumann , 1975Grasso et al 1985Grasso et al , 1990Cuomo et al 1985Cuomo et al , 1988Shearer and Burgos 1987) with fewer studies in more recent years (Petersen and Koch 1997;Panebianco et al 2002;Abdel-Wahab 2011a, b). The most intensive collections were made by Koch and Petersen (1996), Lintott and Lintott (2002), Jones et al (1998), Jones (2010) and AbdelWahab et al 2008 who reported 75 (Denmark), 38 (New Zealand), 92 (Friday Harbour, USA) and 41 (Italy) fungi, respectively.…”
Section: Lignicolous Marine Fungimentioning
confidence: 99%
“…Initialy this was focused on temperate water fungi, especially wood-inhabiting taxa (Jones 1968;Schaumann 1968Schaumann , 1969Schaumann , 1975Grasso et al 1985Grasso et al , 1990Cuomo et al 1985Cuomo et al , 1988Shearer and Burgos 1987) with fewer studies in more recent years (Petersen and Koch 1997;Panebianco et al 2002;Abdel-Wahab 2011a, b). The most intensive collections were made by Koch and Petersen (1996), Lintott and Lintott (2002), Jones et al (1998), Jones (2010) and AbdelWahab et al 2008 who reported 75 (Denmark), 38 (New Zealand), 92 (Friday Harbour, USA) and 41 (Italy) fungi, respectively.…”
Section: Lignicolous Marine Fungimentioning
confidence: 99%
“…Pinus spp. and Fagus sylvatica are woods often used to inventory marine fungi in submerged conditions (Byrne & Jones, 1974;Grasso et al, 1990;Vrijmoed et al, 1982Vrijmoed et al, , 1986Azevedo et al, 2010), because lignocellulosic substrata are colonized throughout submersion by a great variety of lignicolous species.…”
Section: Introductionmentioning
confidence: 99%
“…In temperate waters Lulworthia species are among the most frequently detected fungi in submerged woods (Byrne & Jones, 1974;Mouzouras et al, 1985;Grasso et al, 1985Grasso et al, , 1990Azevedo et al, 2010) and halophytes (e.g. S. maritima) (Barata, 1997).…”
Section: Introductionmentioning
confidence: 99%